PENGARUH EDUKASI GIZI MELALUI MEDIA VIDEO PIRING MAKANKU TERHADAP PENGETAHUAN DAN SIKAP SISWA - Sutrio Sutrio; Andi Eka Yunianto (Poltekkes Kemenkes Mataram, 2021)
Background : The problem of nutrition in adolescents, especially the problem of obesity, is one of the focuses of government attention. Nutrition education is one of the most effective ways to increase the knowledge and attitudes of adolescents to maintain their diet so that obesity does not occur. Purpose : This study purposed to analyze the effectiveness of nutrition education in the video media